Incidence of sexually transmitted infections during pregnancy. - Chloe A Teasdale; Elaine J Abrams; Mary Ann Chiasson; Jessica Justman; Kelly Blanchard; Heidi E Jones (PLoS ONE, 2018)
Prevalence of sexually transmitted infections (STI) is high among pregnant women in certain settings. We estimated STI incidence and compared STI risk in pregnant and non-pregnant women. Data came from the Methods for Improving Reproductive Health in Africa (MIRA) study conducted in South Africa and Zimbabwe 2003-2006. Women aged 18-50 years with at least one follow-up visit within 6 months of enrollment were included. Follow-up visits included laboratory testing for pregnancy, chlamydia, gonorrhea, trichomoniasis, and HIV, as well as self-report of hormonal contraceptive (HC) use, sexual behaviors and intravaginal practices. All visits were classified according to pregnancy status. Incidence of each STI was calculated using follow-up time. Cox proportional hazards models were fitted using pregnancy as a time-varying exposure and sexual behaviors and intravaginal practices as time-varying covariates. Among 4,549 women, 766 (16.8%) had a positive pregnancy test. Median follow-up time was 18 months [IQR: 12-24]. The overall incidence rate of chlamydia was 6.7 per 100 person years (py) and 9.9/100py during pregnancy; gonorrhea incidence was 2.7/100py and 4.9/100py during pregnancy; trichomoniasis incidence was 7.1/100py overall and 9.2/100py during pregnancy. Overall HIV incidence was 3.9/100py and 3.8/100py during pregnancy. In crude models, pregnancy increased risk for chlamydia (hazard ratio (HR) 1.5, 95%CI: 1.1-1.2), however there was no increased risk of any measured STI in adjusted models. STI Incidence was high during pregnancy however pregnancy did not increase STI risk after adjustment for sexual behaviors. Greater efforts are needed to help pregnant women avoid STIs.